Specular Microscopic Corneal Endothelial Cell Changes following Uneventful Phacoemulsification in Patients with Gout - Mortada Abozaid; Rana Saad-eldin; Mahmoud Farouk; Mohamed Anbar; Ehab Wasfi (Journal of Ophthalmology)
Purpose. To assess the effects of phacoemulsification on the corneal endothelium in patients with gout and age-related cataracts. Methods. Eighty-eight patients who underwent uneventful phacoemulsification for age-related cataracts were included in this retrospective comparative study. The patients were divided into two groups: group A included 31 patients with gout and tight control of uric acid levels and group B included 57 patients without gout or any other systemic disease. All patients completed follow-up assessments over 6 months, and the two groups were compared in terms of changes to their specular microscopic values. Results. Both groups showed marked improvement in uncorrected and best-corrected visual acuity at the end of the follow-up period. Corneal endothelial cell loss was more severe in group A than in group B, with a mean difference of 221.35 ± 43.87 in group A and 169.88 ± 52.67 in group B at the sixth month (p < 0.001). The difference between the two groups in terms of other specular microscopic values did not reach statistical significance. Conclusion. Patients with gout are more prone to corneal endothelial cell damage after phacoemulsification than those without gout. To confirm these results, future studies with a prospective design and longer durations of follow-up are needed.